Pengaruh Harga, Lokasi, dan Kualitas Produk Terhadap Kepuasan Pengunjung di Ra Premiere Simatupang Jakarta - Muammar Daffa Alfariz; Liliana Dewi (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
Hotel Ra Premiere Simatupang is one of those in the capital city of Jakarta. This study aims to determine the Effect of Price, Location, and Quality on the satisfaction of visitors who have come and who come to Hotel Ra Premiere Simatupang. In this study, the author analyzes the Effect of Price, Location and Quality of Services in Ra Premier Simatupang Jakarta. This study used a Quantitative-Descriptive method with an approach using Premier data consisting of interviews with customers or visitors who came to Ra Premiere Simatupang and questionnaires from 100 respondents. With model studies, class assumption tests and multiple linear regration tests. The results of this study show that Variabel independent (Price, Location and Product Quality) Positively Affects Visitor Satisfaction at Ra Premiere Simatupang Hotel.